CONSUMER’S PERSONAL TRAITS DISPLAYMENT IN NETWORK MARKETING IN THE CONTEXT OF CONSUMER- SALES CONSULTANT RELATIONS - Aghasyan, N. A. (Արդի հոգեբանություն, 2018)
Within the framework of this article, an experimental analysis of the consumer's personality factors has been carried out, which aims to identify the key personality attributes that affect consumers' involvement in network marketing, as well as the personal traits which are important for effective implementation of the sales consultant-consumer interaction within network marketing. The comparative analysis of the results in the three groups of consumers revealed main features that are important for the implementation of consumer behavior in this marketing field.